Rekindling Vision: Innovative Strategies for Treating Retinal Degeneration - Khan, Irfan; Ramzan, Faiza; Tayyab, Haroon; Damji, Karim F. (International journal of molecular sciences, 2025)
Retinal degeneration, characterized by the progressive loss of photoreceptors, retinal pigment epithelium cells, and/or ganglion cells, is a leading cause of vision impairment. These diseases are generally classified as inherited (e.g., retinitis pigmentosa, Stargardt disease) or acquired (e.g., age-related macular degeneration, diabetic retinopathy, glaucoma) ocular disorders that can lead to blindness. Available treatment options focus on managing symptoms or slowing disease progression and do not address the underlying causes of these diseases. However, recent advancements in regenerative medicine offer alternative solutions for repairing or protecting degenerated retinal tissue. Stem and progenitor cell therapies have shown great potential to differentiate into various retinal cell types and can be combined with gene editing, extracellular vesicles and exosomes, and bioactive molecules to modulate degenerative cellular pathways. Additionally, gene therapy and neuroprotective molecules play a crucial role in enhancing the efficacy of regenerative approaches. These innovative strategies hold the potential to halt the progression of retinal degenerative disorders, repair or replace damaged cells, and improve visual function, ultimately leading to a better quality of life for those affected.